At-Tarâkib Wa Al-Mufaradât Min Khilâli Musalsalah Al-Imâm Ibn Hambal Wa Dauruhâ Fî ‘Ilâji At-Tahajjur Al-Lughawi - Anisah Husna (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
التركيب اللغوي هو الجملة المركبة من عدد من الألفاظ ويلززم أن يؤدي هذا التركيب معنى مفيدا أو مقصودا. المفردات هي أصغر وحدة لغوية التي تدل على معنى معين. كشف التراكيب والمفردات من مسلسلة الإمام أحمد بن حنبل من الحلقة السادسة عشرة إلى الحلقة واحدة وثلاثون. هدفت هذه الدراسة إلى كشف التراكيب والمفردات من مسلسلة الإمام أحمد بن حنبل وطريقة إنجاز هذه الدراسة كانت على منهج علمي الوصفي. وقد أثبتت هذه الدراسة على: مائة وستة عشرة تركيب ومفردة من خلال مسلسلة الإمام أحمد بن حنبل. Lingguistic structure is the compound sentence of a number of words, and this structure must behave a userful or inttened meaning. Vocabulary is te smallest language unit that denotes a spesific meaning. Expose the structures and vocabulary in the series Imam Ahmed bin Hanbal from the sixteenth episode to the thirty-first episode. This study aimed to expose the structures and vocabulary in the series Imam Ahmed bin Hanbal and revealed the extent of its impact in treating linguistic fosilization among the female students of STIBA Ar-Raayah. And the way to accomplish this study was on a scientific method: the analytical description method. This study proved two important results: one hundred and sixteen structures and vocabulary in the series of Imam Ahmed bin Hanbal.